(untitled) (Iranian Journal of Kidney Diseases, 2010)
Introduction. Acquired cystic kidney disease (ACKD) occurs in patients with prolonged uremia, and early detection is important, because clinically significant complications, especially renal cell carcinoma, are associated with ACKD. Materials and Methods. In a cross-sectional study, we evaluated our patients on hemodialysis, in Ahvaz, Iran, using ultrasonography. The criteria for the diagnosis of ACKD were the presence of at least 4 bilateral renal cysts in patients with noncystic primary kidney diseases as the leading cause of kidney failure. Results. A total of 148 patients (95 men and 53 women) were included in the study. The prevalence of ACKD was 20.3% (18.9% in men and 22.6% in women). The mean age in patients with and without ACKD was 60.6 ± 16.8 years and 53.6 ± 14.9 years, and the mean hemodialysis duration was 44.2 ± 18.7 months and 34.3 ± 23.5 months, respectively. There were no significant differences in the frequency of ACKD in the men and the women (P = .59) and in the etiology of end-stage renal disease (P = .64). It was significantly more likely to see ACKD in patients with a history of 3 years or longer being on hemodialysis than in those with a shorter dialysis duration (P = .001). Conclusions. Acquired cystic kidney disease is common in patients on hemodialysis, and we suggest that renal ultrasonography be performed in patients with 3 years or more history of being on renal replacement therapy.